Simulating the Principal-Agent Relationship between Enterprise Owners and Professional Managers Using Evolutionary Game Theory and System Dynamics. (17th July 2021) - Yuan, Liang; Tao, Xiaorui; Ramsey, Thomas Stephen; Degefu, Dagmawi Mulugeta
Abstract : The separation of ownership and management is a common operation mode in modern enterprises, which establishes the principal-agent relationship between modern enterprise owners and professional managers. Due to the information asymmetry and interest conflicts between the principal and agent, the principal-agent problem will occur and affect the efficiency of enterprise operations. Therefore, it is necessary to propose measures to improve the principal-agent relationship. This paper analyzed the principal-agent problem between enterprise owners and professional managers based on system dynamics, evolutionary game, and principal-agent theory and built a principal-agent evolutionary game model to analyze the rule of strategic choices and predict the equilibrium outcomes of different scenarios. In addition, the influence of different factors on strategic choices was simulated by the system dynamics model. The results depicted that the basic benefits and costs of cooperation are the key factors of the strategic choices, and the gap between the expected payoffs of different strategies also affects the probability of choosing those cooperative strategies. Proper supervision, standardization of the managerial labor market, and establishment of long-term incentives are crucial to cooperation between enterprise owners and professional managers.